2022
DOI: 10.1002/ange.202203511
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Simultaneous Identification of Multiple Mitochondrial Reactive Oxygen Species in Living Cells Using a SERS Borrowing Strategy

Abstract: Identification of different mitochondrial reactive oxygen species (ROS) simultaneously in living cells is vital for understanding the critical roles of different ROS in biological processes. To date, it remains a great challenge to develop ROS probes for direct and simultaneous identification of multiple ROS with high specificity. Herein, we report a SERS‐borrowing‐strategy‐based nanoprobe (Au@Pt core–shell nanoparticles) for simultaneous and direct identification of different ROS by their distinct Raman finge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…It is necessary to develop strategies that could detect adsorption configurations and temporal evolution of intermediates and correlate with the reactivity. The configuration evolution of intermediates may profoundly impact the field of chemical catalysis and even biocatalysis 13 and may lead to a decisive step toward the design and fabrication of highly efficient catalytic materials. Surface-enhanced Raman spectroscopy (SERS) is a highly sensitive technique for detecting surface oxygen-containing species, especially in the low wavenumber region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26,27 By its high sensitivity, in situ SERS has been used to detect active species in biological systems by research groups including our group. [28][29][30][31][32][33][34][35] Recently, it begins to emerge in the study of the underlying catalytic reaction mechanisms. [36][37][38] For example, by using bifunctional Au@Ni 3 FeO x structures, the Raman signal from intermediate species (O-O -) during oxygen evolution reaction on Ni 3 FeO x NPs can be enhanced and seen because of the SERS enhancement from the Au core.…”
Section: Introductionmentioning
confidence: 99%